Relações entre as desigualdades sociais e a evasão escolar no ensino médio - Palmero, Isabela Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The present academic work seeks to think about socioeconomic questions of the Brazilian population, discussing socioeconomic level together with population unemployment rates and the job search among young people that are in school age, evaluating how those impact on the dropout indicators among basic education students in Brazil. The profile used will be High School students. The work methodology is based on identifying the collected data in articles and studies, and analyzing them in the light of Pierre’s Bourdieu social theory The work is a qualitative research that seeks to explore the data on unemployment, school dropout and social inequality at the national level, compared to school dropout indicators. Through this analysis, we hope to prove Bourdieu's thesis that social inequality reflects educational inequality, focusing the study on high school students in the Brazilian nation.

O presente trabalho acadêmico buscará refletir acerca das questões socioeconômicas da população brasileira, discutindo nível socioeconômico conjuntamente com as taxas de desocupação da população (desemprego) e de busca de emprego por jovens em idade escolar, avaliando como estas impactam nos indicadores de evasão escolar entre alunos da educação básica no Brasil. O recorte utilizado serão os alunos do Ensino Médio. A metodologia do trabalho resume-se a identificar dados coletados em artigos e estudos, e analisá-los à luz das teorias sociais de Pierre Bourdieu. Trata-se de uma pesquisa qualitativa, que procura explorar os dados sobre desemprego, evasão escolar e desigualdade social em âmbito nacional, frente aos indicadores de evasão escolar. Por meio dessa análise, espera-se comprovar a tese de Bourdieu de que a desigualdade social reflete em desigualdade educacional, focando o estudo nos alunos do Ensino Médio na nação brasileira.
Relations between social inequalities and school dropout in high school
Keywords: School dropout; Unemployment; Rent inequality; High school; Evasão escolar; Desocupação; Desigualdade de renda; Ensino médio